Haemolytic Disease of the Newborn Caused by Anti-Lan Antibody. Issue 5662 (12th July 1969) - Smith, D. S.; Stratton, F.; Johnson, T.; Brown, R.; Howell, P.; Riches, R.
Abstract : The first recorded example of anti-Lan associated with haemolytic disease of the newborn is reported. This emphasizes the importance of screening for atypical antibodies early in pregnancy, even though prophylactic use of anti-D immunoglobulin will eventually reduce the incidence of haemolytic disease due to anti-D antibody.